The Association Between Cardiorespiratory Fitness and Cognition Appears Neither Related to Current Physical Activity Nor Mediated by Brain-Derived Neurotrophic Factor in a Sample of Outpatients With Schizophrenia - Holmen, Tom Langerud; Egeland, Jens; Andersen, Eivind; Mordal, Jon; Andreassen, Ole Andreas; Ueland, Thor; Bigseth, Therese Torgersen; Bang-Kittilsen, Gry; Engh, John Abel (Frontiers in Psychiatry, 2019)
Objective: We investigated whether levels of current physical activity (PA) contribute to the established relationship between cardio-respiratory fitness (CRF) and cognition in schizophrenia, and whether brain-derived neurotrophic factor (BDNF) or its precursor proBDNF mediate this relationship. Method: Sixty-one outpatients with schizophrenia spectrum disorders participated. Neurocognition was assessed with the Wechsler Adult Intelligence Scale (WAIS) and nine subtests from the MATRICS battery comprising a neurocognitive composite score (NCS). CRF was assessed with peak oxygen uptake (VO2peak) measured directly during a maximum exercise test. Current PA levels were objectively assessed by an accelerometer worn for four consecutive days. BDNF and proBDNF were measured in fasting blood. Four serial parallel mediation analyses and two additional parallel mediation analyses were conducted, while controlling for age and sex at all levels. Results: No direct effects were found between PA measures and WAIS or NCS. No significant mediating effects of CRF or BDNF/proBDNF were detected. Conclusion: The results do not support the hypothesis that PA contributes to the naturally occurring relationship between CRF and cognition in schizophrenia, or the hypothesis that BDNF or proBDNF mediate this relationship. The results arguably support the assumption that the association between CRF and cognition in schizophrenia is established developmentally early.